Different Doses, Forms, and Frequencies of Zinc Supplementation for the Prevention of Diarrhea and Promotion of Linear Growth among Young Bangladeshi Children: A Six-Arm, Randomized, Community-Based Efficacy Trial. Issue 5 (7th January 2022) - Islam, M Munirul; Black, Robert E; Krebs, Nancy F; Westcott, Jamie; Long, Julie; Islam, Kazi Munisul; Peerson, Janet M; Sthity, Rahvia Alam; Khandaker, Afsana Mim; Hasan, Mehedi; El Arifeen, Shams; Ahmed, Tahmeed; et al.
ABSTRACT: Background: Children in resource-limited settings remain vulnerable to zinc deficiency and its consequences. Objectives: To evaluate the effects of different doses, durations, and frequencies of zinc supplementation on the incidence of diarrhea and change in linear growth among young children. Methods: We conducted a randomized, partially double-blind, controlled, 6-arm, community-based efficacy trial in Dhaka, Bangladesh. Children aged 9–11 mo were randomly assigned to receive 1 of the following interventions for 24 wk: 1 ) standard micronutrient powder (MNP) containing 4.1 mg zinc and 10 mg iron, daily; 2 ) high-zinc (10 mg), low-iron (6 mg) (HiZn LoFe) MNP, daily; 3 ) HiZn (10 mg) LoFe (6 mg)/HiZn (10 mg), no-iron MNPs on alternating days; 4 ) dispersible zinc tablet (10 mg), daily; 5 ) dispersible zinc tablet (10 mg), daily for 2 wk at enrollment and 12 wk; 6 ) placebo powder, daily. Primary outcomes were incidence of diarrhea and change in length-for-age z -score (LAZ) over the 24-wk intervention period. Home visits were conducted twice weekly to assess diarrhea and other morbidity. Incidence and prevalence outcomes were compared among groups with Poisson regression; continuous outcomes were compared using ANCOVA. Results: A total of 2886 children were enrolled between February 2018 and July 2019. The mean incidence and prevalence of diarrhea among all participants was 1.21 episodes per 100 d and 3.76 d per 100 d, respectively. There were no differences in the incidence or prevalence of diarrhea across intervention groups. The decline in LAZ was slightly smaller among children in the daily HiZn LoFe MNP group compared with the placebo powder group ( P < 0.05). Conclusions: The dose of zinc in MNPs as well as the duration and frequency of supplementation evaluated in this trial were not effective in reducing diarrhea; however, the daily HiZn LoFe MNP formulation offered modest improvements in linear growth among young children. This trial was registered at clinicaltrials.gov as NCT03406793.